Decision Support System Course in Developed and Developing Countries - Akbar, Syaichul Fitrian; Awang, Halizah Binti (Letters in Information Technology Education (LITE), 2020)
This paper reports have three goals to find out: the description of the higher education system in developed countries; the description of the higher education system in developing countries; and the decision support system syllabus in developed and developing countries that related to the higher education system.The development of technology and information has an influence on people's needs and the transformation of the labor market, so higher education is involved in intense competition. For this reason, the higher education system must be dynamic and sustainably able to enter the uncharted domain, so that in order to achieve it, developing countries need to learn about the higher education system in developed countries to improve the higher education system in their country.The method used is descriptive study and critical study taking into account the guidelines proposed by Kitchenham and adjusted to the literature review which consists of 2 main stages, namely planning and implementation. At the planning stage, broadly the selection of studies related to education, research, and information systems with criteria, namely studies published between 2012 and 2018, and studies that describe the higher education system, as well as decision support systems as topics. The study category consists of tertiary education in developed and developing countries, the higher education system when the study is conducted, and the efforts made regarding the higher education system in the country. Content analysis makes it possible to find research trends on a topic. In the event of a difference, resolved through discussion.By highlighting the positive aspects of the picture of the higher education system in developed and developing countries, and the decision support system course as a topic, it is hoped that it can assist in shaping education reform with the assumption that countries are willing to learn from each other about success from other countries.